Cost-consequence model comparing eltrombopag versus romiplostim for adult patients with chronic immune thrombocytopenia - Tremblay G; Dolph M; Bhor M; Said Q; Elliott B; Briggs A (Dove Medical Press, 2018)
Gabriel Tremblay,1 Mike Dolph,1 Menaka Bhor,2 Qayyim Said,2 Brian Elliott,2 Andrew Briggs3 1Department of Health Economics, Purple Squirrel Economics, New York, NY, USA; 2Department of Health Economics and Outcomes Research, Novartis Pharmaceuticals, East Hanover, NJ, USA; 3William R. Lindsay Chair of Health Economics, University of Glasgow, Glasgow, Scotland, UK Background: Thrombopoietin-receptor agonists eltrombopag (EPAG) and romiplostim (ROMI) are treatment options for adults with chronic immune thrombocytopenia (cITP) who have had an insufficient response to corticosteroids or immunoglobulins. Methods: A cost-consequence model was developed to evaluate the costs relative to treatment success of EPAG, ROMI, and watch and rescue (W&R) in previously treated patients. The primary endpoint assessed was severe bleeding, derived from all identified phase III registered clinical trials. Health outcomes were compared via indirect treatment comparison. Costs incorporated in the model included drug and administration, routine care, rescue medications, bleeding-related adverse events, other adverse events, and mortality costs. A trial (26-week) time horizon was used, as certain endpoints used in the model were bound to within-trial results. Results: In the intent-to-treat (ITT) population, the overall estimated cost per patient for EPAG was US$66,560 compared to US$91,039 for ROMI and US$30,099 for W&R. Compared to the ITT population, the difference in cost between EPAG and ROMI was slightly greater in splenectomized patients (US$65,998 for EPAG compared to US$91,485 for ROMI) and slightly less in non-splenectomized patients (US$67,151 for EPAG compared to US$91,455 for ROMI), though the overall trend remained the same. When assessing cost per severe bleeding event avoided in the ITT population, EPAG dominated (less expensive, more effective) ROMI. Sensitivity analyses confirmed these results. Conclusion: EPAG was preferred over ROMI in the treatment of cITP, largely driven by the reduction in severe bleeding events associated with its use. Keywords: chronic immune thrombocytopenia, eltrombopag, romiplostim, cost consequence, cost analysis, USA